A review of the application of virtual reality technology in higher education based on Web of Science literature data as an example - Ding, Xiaoqin; Li, Zhe (Frontiers in Education, 2022)
In recent years, with the rapid development of technology, the immersion and interactivity of virtual reality technology have developed, and researchers are very interested in the application of VR in the field of higher education. This paper adopts the literature analysis method, selects 80 empirical studies in the Web of Science literature database, codes and analyzes the papers from the three dimensions of research context, related technologies and teaching effect evaluation. The research results show that the research objects of VR application in higher education are mainly undergraduates, and the main application majors are science, engineering and medical related majors, and the application of humanities and social science majors such as history and art is relatively rare. At present, the devices used for VR in higher education are mainly computers and head-mounted devices. Although the immersion and interactivity of the devices are improved, the portability of the devices is not enough. In addition, students lack guidance and training in the use of VR equipment before class. Compared with traditional education, most of the studies show that the application of VR in higher education and teaching is positive, mainly by affecting students' behaviors to affect students' learning results and researchers mainly use traditional evaluation methods to evaluate teaching effects, use questionnaires and tests to collect data, and mainly use difference analysis and descriptive analysis for data analysis. Based on the research results, the researcher puts forward some suggestions at the end of the article, hoping to help deepen the application of VR in higher education.